2019
DOI: 10.1007/s11440-019-00843-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the effects of groundwater drawdown on ground settlement for excavation in residual soils

Abstract: For deep excavations in residual soils that are underlain by highly fissured or fractured rocks, it is common to observe the drawdown of the groundwater table behind the excavation, resulting in seepage-induced ground settlement. In this study, finite element analyses are firstly performed to assess the critical parameters that influence the ground settlement performance in residual soil deposits subjected to groundwater drawdown. The critical parameters that influence the ground settlement performance were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(17 citation statements)
references
References 36 publications
0
16
0
1
Order By: Relevance
“…Research on land subsidence is topical in engineering and environmental research, as its impacts are observed in many countries including China, Iran, Japan, Singapore, Thailand and the USA (Ye et al 2015;Nadiri et al 2018a;Hayashi et al 2009;Phien-wej et al 2006;Zhang et al 2018;Goh et al 2019;Galloway et al 1999). Some engineering impacts of subsidence are outlined by Kihm et al (2007), which include the following: (i) a collapse of water wells and the breakage of their casings and ancillary works by compacted soil due to decline of the water table in aquifers; (ii) the requirement for realignment of diversion structures in open channels; (iii) redistribution of stresses and strains in building works and structures creating the potential for excessive forces and subsequent failures.…”
Section: Introductionmentioning
confidence: 99%
“…Research on land subsidence is topical in engineering and environmental research, as its impacts are observed in many countries including China, Iran, Japan, Singapore, Thailand and the USA (Ye et al 2015;Nadiri et al 2018a;Hayashi et al 2009;Phien-wej et al 2006;Zhang et al 2018;Goh et al 2019;Galloway et al 1999). Some engineering impacts of subsidence are outlined by Kihm et al (2007), which include the following: (i) a collapse of water wells and the breakage of their casings and ancillary works by compacted soil due to decline of the water table in aquifers; (ii) the requirement for realignment of diversion structures in open channels; (iii) redistribution of stresses and strains in building works and structures creating the potential for excessive forces and subsequent failures.…”
Section: Introductionmentioning
confidence: 99%
“…Although groundwater control measures have been taken, it is observed that the groundwater level behind the side wall will gradually decrease with the increase of excavation depth. Due to the decrease of groundwater level, obvious ground settlement was observed 35 . The increase of ground settlement will increase the soil loss, which will reduce the reliability.…”
Section: Resultsmentioning
confidence: 99%
“…When a joint in a D-wall does contain defects, leakage may occur. If the excavation is below the groundwater table, there is the possibility that water inrush and piping may occur during excavation, resulting in land subsidence and even disaster [ 6 , 7 , 8 , 9 , 10 ]. Furthermore, the bearing capacity of the foundation will decrease with the inrush of groundwater into the excavation zone [ 11 ].…”
Section: Introductionmentioning
confidence: 99%